MATHEMATICAL MODELLING FOR DRYING OF SAWDUST IN A TRIPLE PASS ROTARY DRYER - Papuga, S.; Petrović, P.; Maksimović, M. (Journal of Engineering & Processing Management, 2009)
Today, rotary dryers are often use to dry sawdust prior to their further processing, palletizing and briquetting, into commercially voluble product. This paper present mathematical model for drying process of sawdust particles in a triple pass rotary dryer. As basis for this model, we used existing mathematical models for drying of sawdust and other biological materials in a single pass rotary dryer, which are modified and extended in order to satisfy mathematical description of motion of material in the triple pass rotary dryer. Developed mathematical model is used as basis for further developing of the simulation model that predict temperature and moisture profile sawdust and drying along the dryer. In order to solve and validate developed rotary dryer model, commercial triple pass rotary dryer, installed in enterprise Panensa near town of Srbac, have been analysed, and measured sawdust drying data have been used for comparison. Comparison between predicted and the measured results were good. Mathematical model i.e. rotary dryer simulation model developed in this paper is going to enable better management and controlling of process in the mentioned commercial rotary dryer as well as in other rotary dryers for wood waste with modification of appropriate model parameters.